Analysis of the Quality of Health Services Based on the Implementation of Accreditation on Patient Satisfaction at Puskesmas Teminabuan, South Sorong Regency - Sirenden, Intan; Ilyas, Muh; Chandra, Freddy; Zamli, Zamli (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Quality health services are a basic need and expectation for all individuals seeking care. Health facilities are expected to meet patient expectations through service delivery. Objective: This study aimed to evaluate health service quality based on accreditation implementation across five dimensions responsiveness, assurance, tangibility, empathy, and reliability and their effect on patient satisfaction. Methods: A quantitative study with a cross-sectional design was conducted at the Teminabuan Health Center, South Sorong Regency. A total of 92 patients participated, and data were collected using a structured questionnaire assessing satisfaction across the five service quality dimensions. Results: Partial analysis showed that assurance and tangibility significantly influenced patient satisfaction (p < 0.05), while responsiveness, empathy, and reliability did not (p > 0.05). The F-test indicated a significant simultaneous effect of all five dimensions on satisfaction (p = 0.000 < 0.05). Conclusion: The five dimensions of service quality collectively impact patient satisfaction at Teminabuan Health Center. However, assurance and tangibility were the only dimensions with a significant partial effect. These findings highlight the need to strengthen specific service aspects to enhance overall patient satisfaction.